Development of a New Colorimetric, Kinetic and Automated Ceruloplasmin Ferroxidase Activity Measurement Method - Salim Neşelioğlu; Esra Fırat Oğuz; Özcan Erel (MDPI AG, 2022)
Background: Ceruloplasmin plays an important role in the regulation of iron metabolism. Ceruloplasmin is an acute-phase protein known to have many metabolic effects. Its activity increases during infection, inflammation, and compensation of oxidation. In the current study, our aim is to develop a new method for the measurement of ferroxidase activity without requiring any chromogen. Methods: Venous blood samples were collected into serum separator tubes. Ferric iron ions formed by the enzyme ferroxidase were measured, both manually and fully automatically, at the 415 nm wavelength without using chromogen. These results were compared to conventional ferroxidase measurement methods and to the immunoturbidimetric ceruloplasmin measurement method. Results: The detection limit of the new assay was 14.8 U/L. The upper limit of the linearity was 1380 U/L. Precision values were calculated for high, medium, and low levels of ferroxidase activity in serum pool. The coefficient of variation was <5% for each level. Conclusion: In the present method, chromogens are not used. With its considerably low cost and short reaction time, this method is able to provide fast results, can be performed easily, and makes accurate measurements.